Optimization of the cooling system of electric vehicle batteries (2022)
The most important components of electrical vehicles are the battery and the related cooling system. These subsystems play a major role in determining the overall electric vehicle performances. In this study, a novel cooling system with fluid in the battery cell is proposed, by which the energy storage system can be optimized through control of the temperature of the batteries. A sensitivity analysis is conducted considering the maximum temperature, the heat rate, the coolant temperature, and the geometry of the cavities. The numerical simulations show that the parameters for the trapezoidal compartment have an impact on the thermal performance of battery. An optimal geometry is proposed accordingly. It is concluded that for high values of Reynolds number for which the flow becomes turbulent, a decrease in the battery temperature can be obtained thereby avoiding thermal stresses.